Teknologi dan Produksi Akuakultur di Danau Tondano Kabupaten Minahasa - Mambrasar, Deni; Salindeho, Indra R.N; Tumembouw, Sipriana (e-Journal BUDIDAYA PERAIRAN, 2014)
The aim of this study was to know theÂ  applied technology and the production value of the aquaculture activities in the waters of Â Lake Tondano and to identify factors influencing aquaculture production in Tondano lake. Data collectedÂ  consisted of primary andÂ  sekunder data. Â Primary data Â were collected by conducting a survey to fish-farmers as respondents around the lake Tondano. Â Operational aquaculture data were obtainedÂ  by interviewing the fish farmers and by observation. Â Secondary data were collected from variousÂ  institution Â such as MinahasaÂ  Fisheries Â OfficeÂ  ,Â  Office ofÂ  Village Head and Fish-farmer Â GroupÂ  Administrative Centre.Â  Collected data were Â descriptively analyzed Â and presented in the form of tabulation and various model of diagram.Â  Fluctuated data in aquacultural production valueÂ  and the number ofÂ  operatedÂ  KJT Â during the periood of Â 2001 to Â 2014 was analysed by using linear regression Â and correlation. The aquacultral production value Â of the lake Tondano inÂ  2014 was Â estimated only 1227,3 tons /year. Â The number of operated Â KJT Â only remained 1203 units. Â The production value decreased consistentlyÂ  from 2003 to 2014.Â  Â Statistical analysis showed that during Â 2001-2014 there was a reduction about 1.236 ton every year in aquacultural production, and Â 607 units of operated KJT.Â  There was a Â very strong correlation Â between Â time Â (year) and the Â the aquacultural production, and also between Â time (year) andÂ  the number Â ofÂ  operated KJT.Â  There were 3 important Â factors Â influencing the aquacultural production value of lake Tondano, which were: environmental, technical and economic factor.Â Â  However, the primary factor Â wasÂ  â€˜economicâ€™ factor.Â  The Â â€˜very high priceâ€™ of the fish formulated diet Â and Â the "very low priceâ€Â  ofÂ  the produced fish were the main causes of the problem. Â Â The fish farmers could not afford the invesment and operational cost.Â Â  Environmental degradation ofÂ  Lake Tondano watersÂ  also significantlyÂ  influenced the operation of aquacultural activities. Â  Keywords:Â  Production, technology, aquaculture, Lake Tondano